1964
DOI: 10.1083/jcb.20.1.25
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between the Intracellular Ribonucleic Acid Distribution and Amino Acid Incorporation in the Liver of the Developing Chick Embryo

Abstract: The RNA-P and DNA-P content of the nucleus and the RNA-P content of the whole cell of the livers of 8-to 20-day chick embryos and of adult fowls have been determined. The DNA-P content of the liver nuclei was slightly higher in the 8-and 10-day embryo than in all the other stages examined. A significant decrease in the RNA content of the cell occurred during embryonic development. The RNA content of the adult cell was the same as that of the 14-to 16-day embryo. The proportion of the cellular RNA contributed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…To isolate the DNA component we measured RNase treated cells, and determined a G1 DNA mass of 7.4 pg. These results are consistent with the published numbers for the genomic DNA and the RNA/DNA ratio measured in similar CHO cells using flow cytometry and Feulgen densitometry (16, 2123, 31, 4243). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To isolate the DNA component we measured RNase treated cells, and determined a G1 DNA mass of 7.4 pg. These results are consistent with the published numbers for the genomic DNA and the RNA/DNA ratio measured in similar CHO cells using flow cytometry and Feulgen densitometry (16, 2123, 31, 4243). …”
Section: Discussionsupporting
confidence: 91%
“…While the qualitative features of the histograms are quite similar to cytometry data for both algorithms (2021, 34), some problems in terms of statistical broadening and absolute calibration appear for the classical 260/280-nm data reduction. For the nucleic acid by this classical algorithm, there is a well-shaped histogram (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Nuclei (1) and mitochondria (55, 61) possess recognized mechanisms for production of proteins . When expressed as grain concentration per unit area (Table I), the 4 min values for nuclei and mitochondria are below the average for liver, in accord with the lower incorporation of labeled amino acids into nuclei and mitochondria found when these components were isolated after labeling (14,36,54) .…”
Section: Discussionmentioning
confidence: 61%
“…Protein synthesis was 20 times faster in the fetal kidney than in the adult kidney ( Fig. 4 a); Duck-Chong et al (28) found a difference of a similar magnitude between fetal and adult liver in the chick. The apparent 100-fold difference between fetal and adult kidney shown in Fig.…”
Section: Protein Synthesismentioning
confidence: 82%